Origin of thermal depolarization in piezoelectric ceramics. (1st April 2016) - Liao, Qingwei; Huang, Panfeng; An, Zhao; Li, Dan; Huang, Haining; Zhang, Chunhua
Abstract: PZT, BSPT, PT, and two lead-free Bi2 WO6, as five of the most representative piezoelectric systems with different Curie points were selected to study the origin of thermal depolarization in piezoelectric ceramics. The temperature dependences of dielectric loss and dielectric constant curves show that dielectric loss peaks of PZTMN, BSPTPNW, PTBFM, BWLi, and BWLa are at 330 °C, 392.2 °C, 495 °C, 598.8 °C, and 781 °C, respectively. The results of thermal depoling measurement show that the depolarization temperature is closely related to the dielectric loss peak. And the peak points of dielectric loss curves below or at the Curie temperature are the points of complete depolarization. Graphical abstract: The temperature dependences of dielectric loss (right Y) and dielectric constant (left Y) of the PZTMN (a), BSPTPNW (b), PTBFM (c), BWLi (d), BWLa (e) ceramics. The peak points of dielectric loss curves below or at the Curie temperature are the points of complete depolarization.